Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 3/5 x=4/7+1/5; b)(2x-1/2):3=12;
3/5 x=27/35 (2x-1/2)=12x3
x=27/35:3/5 2x-1/2=36
x=9/7 2x=36+1/2
Vay x=9/7 2x=73/2
x=73/2:2
x=73/4
Vay x=73/4
\(\frac{3}{x-5}=-\frac{4}{x+2}\)
=> 3 ( x + 2 ) = 4 ( x - 5 )
=> 3x + 6 = 4x - 20
=> 3x - 4x = - 6 - 20
=> - 1x = - 26
=> x = 26
1) 3/x-5=-4/x+2
3x+6=-4x+20
7x . =14
x . =2
2) x+3/-4=-9/x+3
(x+3)^2=36
Ta có hai trường hợp:
*x+3=6=)x=3
*x+3=-6=)x=-9
a, \(x\) \(\times\) \(\dfrac{1}{2}\) - \(\dfrac{3}{4}\) = \(\dfrac{5}{6}\)
\(x\) \(\times\) \(\dfrac{1}{2}\) = \(\dfrac{5}{6}\) + \(\dfrac{3}{4}\)
\(x\) \(\times\) \(\dfrac{1}{2}\) = \(\dfrac{19}{12}\)
\(x\) = \(\dfrac{19}{12}\) : \(\dfrac{1}{2}\)
\(x\) = \(\dfrac{19}{6}\)
b, \(x\) : \(\dfrac{1}{2}\) - \(\dfrac{3}{4}\) = \(\dfrac{5}{6}\)
\(x\): \(\dfrac{1}{2}\) = \(\dfrac{5}{6}\) + \(\dfrac{3}{4}\)
\(x\) : \(\dfrac{1}{2}\) = \(\dfrac{19}{12}\)
\(x\) = \(\dfrac{19}{12}\) \(\times\) \(\dfrac{1}{2}\)
\(x\) = \(\dfrac{19}{24}\)
c, \(x\) \(\times\) \(\dfrac{3}{4}\) + \(x\) \(\times\) \(\dfrac{1}{4}\) = \(\dfrac{7}{8}\)
\(x\) \(\times\) ( \(\dfrac{3}{4}\) + \(\dfrac{1}{4}\)) = \(\dfrac{7}{8}\)
\(x\) \(\times\) 1 = \(\dfrac{7}{8}\)
\(x\) = \(\dfrac{7}{8}\)
d, \(x\times\) \(\dfrac{3}{4}\) - \(x\) \(\times\) \(\dfrac{1}{4}\) = \(\dfrac{7}{8}\)
\(x\) \(\times\) ( \(\dfrac{3}{4}\) - \(\dfrac{1}{4}\)) = \(\dfrac{7}{8}\)
\(x\) \(\times\) \(\dfrac{1}{2}\) = \(\dfrac{7}{8}\)
\(x\) = \(\dfrac{7}{8}\) : \(\dfrac{1}{2}\)
\(x\) = \(\dfrac{7}{4}\)
a) (x + 5/6) . 12/5 - 5/4 = 35%
=> (x + 5/6) . 12/5 = 7/20 + 5/4
=> (x + 5/6) . 12/5 = 8/5
=> x + 5/6 = 8/5 : 12/5
=> x + 5/6 = 2/3
=> x = 2/3 - 5/6
=> x = -1/6
b) 3.(x - 1/2) - 5.(x + 3/5) = -x + 1/5
=> 3x - 3/2 - 5x - 3 = -x + 1/5
=> -2x - 9/2 = -x + 1/5
=> -2x + x = 1/5 + 9/2
=> -x = 47/10
=> x = -47/10
c) 5/2 - 3.(1/3 - x) = 1/4 - 7x
=> 5/2 - 1 + 3x = 1/4 - 7x
=> 3/2 + 3x = 1/4 - 7x
=> 3/x + 7x = 1/4 - 3/2
=> 10x = -5/4
=> x = -5/4 : 10
=> x = -1/8
d) 1/2x + 4/5 .(5/2 + x) = 15/4
=> 1/2x + 2 + 4/5x = 15/4
=> 13/10x = 15/4 - 2
=> 13/10x = 7/4
=> x = 7/4 : 13/10
=> x= 35/26
`4 (x - 1) - 3(x - 2) = -5`
`4x - 4 - 3x + 6 = -5`
`x + 2 = -5`
`x = -5 - 2`
`x = -7`
\(\text{4(x-1)-3(x-2)=-5 }\\ \left(4x-4\right)-\left(3x-6\right)=-5\\ 4\text{X}-4-3x+6=-5\\ \left(4x-3x\right)+\left(-4+6\right)=-5\\ \text{X}+2=-5\\ \text{X}=-5-2=-7\)